(untitled) - Alcock, Rutherford (London, 1978)
Ending centuries of isolation, the Meiji era opened Japan to the world in the late nineteenth century. First published in English in 1893, this translated work by French painter Félix Régamey (1844-1907) offers an artist's perspective on Japanese art and customs, which were an object of fascination to the West.
Keywords: Art,Decorative arts,Nghệ thuật,Nghệ thuật trang trí; Japan,Japan,Nhật Bản,Nhật Bản